POLA PESAN POLITIK PEREMPUAN DI FACEBOOK TERKAIT PEMILIHAN PRESIDEN REPUBLIK INDONESIA 2019 - Linda Andriani (JSSH (Jurnal Sains Sosial dan Humaniora), 2021)
Presidential elections in Indonesia are practices of Indonesian democracy that are interesting to be discussed in the community, especially for women. The research objective was to dismantle the political message patterns in women's participatory communication patterns through the use of Facebook. in the Presidential Election of the Republic of Indonesia in 2019. This research uses the Action Assembly Theory. This is a descriptive qualitative research with a constructivist paradigm and a Netnographic method. The results showed that the pattern of women's political messages on the Facebook wall was a woman's actions in the form of support for both Candidate Pairs of Presidential and Vice-President Candidates 01 and 02 or rejection of Candidate Pairs of Presidential and Vice-President Number 01 or 02. Researchers also found that nowadays it is important for women to master digital literacy and the Law on Information and Electronic Transactions (ITE Law). Keywords: